The Relationship of Body Mass Index (BMI) with The Result of A Six-Minute Walk Test Elderly Pilgrims at Saiful Anwar General Hospital Malang - TR Makhmud (ACI (Acta Cardiologia Indonesiana), 2017)
Background: In the last 2 decades the mortality rate of Indonesian pilgrims is 200-380 deaths per .....